(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2022)
The green seaweed Caulerpa can be found in almost every coastal area of Indonesia, and it is one of the seaweeds with immense potential to be developed in the future. The chemical factors, especially water nutrients (nitrate, nitrite, phosphate, and ammonia), play an essential role in the distribution and diversity of seaweed. This study aimed to identify the abundance, ecological index, and relationship between the water column nutrients concentration and the biodiversity of Caulerpa from three different locations (Bintan Island, Jepara, and Osi Island). There were 12 points of observation at each site. The result showed a correlation between the nutrient levels and the abundance and diversity of Caulerpa in three locations. The nitrate, ammonia, and DIN:P ratio values were significantly different between areas. In contrast, there were insignificant differences in nitrite and phosphate concentrations between sites. The highest nitrate and phosphate concentrations were observed on Osi Island. The nitrite and ammonia values were identical for the condition on Bintan Island. The nitrate value was the main characteristic that distinguished the water nutrient at all sites. The Caulerpa species found in this research were Caulerpa racemosa, Caulerpa lentilifera, Caulerpa serrulata, Caulerpa sertularoides, and Caulerpa cupresoides. The nitrate and phosphate values influenced the growth factor of the green seaweed Caulerpa lentilifera. Caulerpa racemosa and Caulerpa serrulata, on the other hand, grew in response to ammonia levels. Caulerpa cupresoides diversity and abundance were impacted by the nitrite value. The results of the canonical correspondence analysis revealed that nitrate, phosphate, and ammonia were the most important factors influencing Caulerpa distribution in three locations.